2008
DOI: 10.1007/s00128-008-9570-y
|View full text |Cite
|
Sign up to set email alerts
|

QSAR for Predicting Joint Toxicity of Halogenated Benzenes to Dicrateria zhanjiangensis

Abstract: In this study, the toxicity of 49 mixed halogenated benzenes to Dicrateria zhanjiangensis was determined and the partition coefficient of these mixtures was described by using the C(18)-Empore disks/water partition coefficient (K(mix)). According to these data, a simple K(mix)-based QSAR model was successfully used to correlate the toxicity of the mixed halogenated benzenes to D. zhanjiangensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…40 It revealed that the octanol-water partition coefficients (log K ow ) correlated well with the toxicity of chemicals. 41 The order of log K ow was 2,4-dinitrotoluene (1.98) < chlorobenzene (2.89) < p-dichlorobenzene (3.44) < 1,2,3-trichlorobenzene (4.05) < hexachlorobenzene (5.2), and the genotoxicity potential of the above chemicals showed a good consistency with the values of log K ow . 42 The D pc of these benzene derivatives at the developed biosensor greatly matches with the toxicity potential of these analytes showing that the dsDNA/Au biosensor has a great potential for rapid and efficient evaluation of the genotoxicity of chemicals, and it is in agreement with our previous study.…”
Section: Application To Benzene Derivatives For Genotoxicity Potentia...mentioning
confidence: 80%
“…40 It revealed that the octanol-water partition coefficients (log K ow ) correlated well with the toxicity of chemicals. 41 The order of log K ow was 2,4-dinitrotoluene (1.98) < chlorobenzene (2.89) < p-dichlorobenzene (3.44) < 1,2,3-trichlorobenzene (4.05) < hexachlorobenzene (5.2), and the genotoxicity potential of the above chemicals showed a good consistency with the values of log K ow . 42 The D pc of these benzene derivatives at the developed biosensor greatly matches with the toxicity potential of these analytes showing that the dsDNA/Au biosensor has a great potential for rapid and efficient evaluation of the genotoxicity of chemicals, and it is in agreement with our previous study.…”
Section: Application To Benzene Derivatives For Genotoxicity Potentia...mentioning
confidence: 80%
“…A single study [86] employing an integral, non-additive approach was retrieved. Within, toxicity of a series of binary 1:1 combinations consisting of simple substituted benzenes was modelled through use of quantum chemical descriptors.…”
Section: Integral Non-additivementioning
confidence: 99%
“…Zeng等人 [14] 采用logK MD 建立了混合卤代苯对湛 江叉鞭金藻的毒性预测QSAR模型: [9] 则利用该参数建立了混合卤代苯对明 亮发光杆菌的毒性预测QSAR模型: [4] 还采用该参数建立了海洋有机污染物 对明亮发光杆菌的混合毒性预测QSAR模型: [20] 采用该参数建立了全氟羧酸对明亮 发光杆菌混合毒性预测的QSAR模型:…”
Section: 基于Logk MD 的非极性麻醉型化合物混合毒性 预测模型unclassified